Dissociation of rewarding and dopamine transporter-mediated properties of amphetamine - Budygin, Evgeny A. (National Academy of Sciences, 2004)
The interaction of amphetamine (AMPH) with the dopamine (DA) transporter (DAT) is thought to be critically important for the DA-elevating actions of this drug. It is commonly believed that DA elevations are involved in the rewarding/reinforcing properties of AMPH and other drugs of abuse. Here, we found that DAT deletion did not eliminate the rewarding effects of AMPH as measured by conditioned place preference (CPP). In fact, mice in which the DAT gene has been deleted (DAT-KO mice) exhibited AMPH-induced CPP for many weeks after the time when extinction occurred in WT mice. Moreover, systemic AMPH still increased extracellular DA in the nucleus accumbens (NAc) of mice lacking the DAT, although local infusion of AMPH into the NAc did not have this effect. By using voltammetry in NAc slices, we found that AMPH did not decrease the rate of DA clearance. The rate of ventral tegmental area DA neuron firing was dramatically inhibited by AMPH in brain slices from WT mice, but there was no inhibition of firing in DAT-KO mice. AMPH-induced CPP was abolished by pretreatment with WAY-100635, a serotonin 5-HT(1A) receptor antagonist, in DAT-KO mice, but the drug did not change AMPH place preference in WT mice. Therefore, despite the absence of the DAT, AMPH displays rewarding effects and causes an increase in extracellular DA in the NAc of DAT-KO mice, acting indirectly in this case. The 5-HT system may be involved in the rewarding effects of AMPH in these mice.